Investigation of an Outbreak of Hepatitis A in a Coastal Area, Kerala, Southern India - Sandhya Raveendran; P. S. Rakesh; Soumya Dev; Nithin Vijayakumar; Prathibha Prasannakumar (SAGE Publishing, 2016)
An outbreak investigation was initiated following an unusual occurrence of hepatitis A reported among people residing in the coastal belt of Vadi to Vedikunnu area, Kollam district, Kerala, southern India. The time frame of disease occurrence, pattern of its distribution, and the incubation period of hepatitis A infection indicated the probability of occurrence of the outbreak as a result of pipe line water contamination due to mixing of sewage from a canal. The results add evidence to the epidemiology of hepatitis A in the state and warrant the establishment of an efficient water quality surveillance system.